(untitled) (Architecture Image Studies, 2024)
Digital technology has produced radical changes in behavior. Through smartphones, we no longer live in the here and now that makes each moment a present outside of time. We move into states of alternative consciousness, which are states of concentration and states of distraction. We are here and there, without being fully anywhere. This notion of space has been disrupted by the irruption of virtual realities, with tools that allow immersion in simulated realities that have the potential to transform faster than what our senses could encompass with the real body. Architectural designers have found tools for drawing and immersion in imaginary spaces that transform in real time according to the needs of a clientele or creation projects. This is how today we can, through virtual images, simulate architectural spaces to represent work spaces. This potential of the virtual gives rise to activities such as those of the so-called « digital nomads, who are professionals who break the barriers of presence in sectors such as technology, programming, digital marketing, design or consulting. » We will show the other side of this development of the virtual world by studying the architectural setting of the city of Wuhan. The health crisis that produced profound changes in behavior and work activities allowed the development of "remote" activities that at the time off-set the needs of employment and services due to the impossibility to be present. Having been actors at the very heart of the origin of this crisis as was Wuhan, we are living a real experience of the aftermath that these limitations of remote work brought, and the temporary alternatives used to overcome the crisis. Today, we see the negative effects on the population expressed through self-absorbed, internalized and abstracted behavior from the real environment due to continuous immersion in phones and digital devices. There are also negative effects seen in the physical space of the city with the drop in real estate investment and construction. We will, through our experience as photographic researchers in architecture and urban scenery, present the way in which a before and after of the crisis is represented in the architecture under construction. We will see the image of a city that was promised daily changes and that now shows a static construction where the skeletons of unfinished and abandoned buildings are widespread in the city, producing an unprecedented archeology emerging in the urban scenery. In this way, a ubiquity of time and space will appear. Spaces of non-place (non-lieux), which are there but are not and do not offer any function. And only nature can recover its rights.